ЎЗБЕКИСТОН РЕСПУБЛИКАСИ ОЛИЙ ТАЪЛИМ ТИЗИМИДА CBI ВА STEM ТЕХНОЛОГИЯСИГА АСОСЛАНГАН ДАРСНИ ТАШКИЛ ҚИЛИШНИНГ ИЛМИЙ-НАЗАРИЙ АСОСЛАРИ - Машарипова, Ф. (SCIENCE and SOCIETY, 2022)
This article discusses the results of local successful research investigations in ESP that resemble some elements of CBI / STEM technology and opinions on the effectiveness of scientific and practical experiments, which are the basis for the organization of teachingEnglish for biology students using СBI / STEM technologies.